Legal mechanisms for the implementation of human rights in the educational environment - Shakirova, A.B. (Bulletin of the Karaganda University “Law Series”, 2022)
The article reveals the legal mechanism for implementing human rights in the educational environment and examines the main features of this institution. The analysis and generalization of theoretical and empirical materials are carried out through general and special research methods. The study results are the identification of trends in the development of individual rights in the educational environment and the prospects for further improvement of legislation in the field of education. Human rights in education regulate social relations connected with any forms of education and upbringing and form legal mechanisms for implementing human rights. The study aims to examine the legal mechanisms of human rights implementation in the educational environment and to reveal the specifics of human rights protection and enforcement in the educational environment. The article presents the analysis and the current state of the institute of guarantees of human and civil rights and freedoms in the implementation of a citizen’s right to education. The problems of significance and practical realization of the citizen’s right to education are studied and the ways of solving the problem of full and qualitative assurance of the constitutional right of citizens to education in the conditions of statehood formation and democratic society development are offered.